Supply chain management : a study on plastic recycling at United Plastic Recovery Sdn Bhd / Valerie Sinti, Norliza Dzulkifli and Norhismawati Lot - Sinti, Valerie; Dzulkifli, Norliza; Lot, Norhismawati (2014)
The purpose of this study is to identify the current purchasing, transformation and logistic process at UPR ; to examine the issues pertaining to the purchasing, transformation and logistic process at UPR; and to provide recommendation to UPR to have good supply chain management at United Plastic Recovery Sdn. Bhd., Kota Kinabalu, Sabah. Ultimately, this study also aims to identify the company's Supply Chain Management (SCM). For the purpose of this study, a qualitative method is used to collect information whereas a case study approach is used in this study to conclude the findings. Data collection was done through interview and observation. Time-Function Mapping and SWOT Analysis were selected to analyse the findings. The findings indicated that the current purchase and transformation process practiced by UPR take less than one day to run the company daily business. However, the finished products (inventory) are kept at UPR' factory for 26 days before being transport to customers location and become issue for the company. This study proposed UPR to reduce time taken for transporting PET flakes to the customers from 26 days to 14 days.